(untitled) (Almanack, 2021)
As is well known, opium was a major colonial commodity. It was linked to trade in several other commodities of the modern era such as tea, sugar and cotton and through these to Atlantic the slave trade. The movement of these commodities across continents shaped capitalism in very specific ways. In the case of India, for instance, earnings from the several components of the opium enterprise played an important role in the growth of industrial capitalism. This paper looks at the historical circumstances in which various localities and regions of the Indian subcontinent, especially western India, and the Indian Ocean became part of the opium enterprise during the early nineteenth century. It attempts to understand the manner in which local destinies were linked to the global, reinforcing and/or resisting British imperial interests. For this purpose I have chosen the port of Daman, on the West Coast of India as a representative example. Daman (Damaõ) was a Portuguese colony. The paper pays close attention to political processes at the local level so as to make sense of global patterns of trade in a commodity that was vital for sustaining the British Empire.